Development of an Objective and Transparent Islamic Religious Education Learning Assessment Rubric - Mukarromah, Wardatuz Zahro’ul; Azanabilah, Taqiyyatunnisa Maulidy; Wulandari, Siti; Halimah, Siti (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
The development of assessment rubrics in Islamic Religious Education (PAI) is an essential effort toward establishing an objective, transparent, and character-oriented evaluation system rooted in Islamic values. This study aims to design assessment rubrics that holistically measure cognitive, affective, and psychomotor dimensions. The Research and Development (RD) method applies a modified Borg Gall model, including needs analysis, prototype design, expert validation, limited trials, product revision, and large-scale implementation. Data were analyzed qualitatively and quantitatively using expert judgment, Aiken’s V, and Cronbach’s Alpha to assess validity and reliability. The findings indicate that analytic rubrics improve the objectivity and consistency of assessment, particularly in evaluating attitudes and worship performance. Providing rubrics to students enhances learning motivation, accountability, and academic honesty. The use of digital platforms, such as e-rubrics and digital portfolios, strengthens documentation and feedback effectiveness. The study concludes that successful rubric implementation depends on teacher involvement, clear indicators, scoring calibration, and institutional support. The developed rubric serves as a foundational instrument for fair, adaptive, and spiritually oriented PAI evaluation toward nurturing insan kamil—a fully developed Muslim individual.